Escritores hispanoamericanos de hoy - Baquero, Gastón. 1914-1997
Contiene: Rubén Darío, José Vasconcelos, Gabriela Mistral, Vicente Huidobro, Alfonso Reyes, Porfirio Barba Jacob, Pablo Beruda, Fernando González, César Vallejo, Francisco Romero, Alfonso Junco, Erico Verissimo, Jorge Luis Borges, Alejo Carpentier, Ignacio B. Anzoátegui, Eduardo Caballero Calderón, Gabriel García Márquez, Germán Arciniegas